A new look at Pleurotomaria perlata Hall, 1852 (Gastropoda) from the Silurian of Laurentia. (3rd July 2018) - Peel, John S.
Abstract: New material from Genoa, Ohio, USA, of the distinctive but poorly known Silurian gastropod Pleurotomaria perlata Hall, 1852, originally described from the Guelph Formation of Ontario, Canada, demonstrates that it is not a pleurotomariinid vetigastropod. It is a species of Isfarispira Gubanov, Peel & Pianovskaya, 1995, first described from the Silurian of Kyrgyzstan, central Asia, and now recognised from Laurentia. Isfarispira belongs within a pycnomphaline–omphalotrochid group of euomphaloidean gastropods but this group is too poorly understood to allow firm placement at this time.